Kendala Dalam Perjanjian Sewa Kapal TUGBOAT dan BARGE 230 Feet Sebagai Alat Angkut Muatan Batu Boulder Di Perairan Indonesia dan Upaya Penyelesaiannya - Martin Mangunsong; Marthin Loies; Mohammad Wira Utama (Rampai Jurnal Hukum (RJH), 2023)
One of the sea transportations that is really needed is transport ships, both from domestic and overseas routes. The mechanism for using ship transportation via rental or charter routes will carry out an agreement that is outlined in concrete form in the form of a charter agreement. The formulation of the problem discussed is the obstacles in the rental agreement for the 230 feet Tugboat and Barge as a means of transporting boulders and legal efforts to overcome obstacles in the rental agreement for the 230 feet Tugboat and Barge as a means of transporting boulders. The conclusion in this research, regarding the obstacles in the 230 feet Tugboat and Barge rental agreement as a means of transporting boulders, is the lack of legal awareness of the second party in understanding the contents of the agreement clauses, especially Articles III and Notary regarding the contents of the agreement clauses, resulting in disputes for the parties in the agreed agreement. Legal efforts to overcome obstacles in the 230 feet Tugboat and Barge rental agreement as a means of transporting boulders in Indonesian waters by applying good faith in carrying out achievements (rights and obligations) and writing the rental agreement into an authentic deed before a Notary.  Abstrak Mekanisme penggunaan transportasi kapal melalui jalur sewa atau charter, akan melakukan perikatan yang dituangkan di dalam bentuk konkrit berupa surat perjanjian sewa. Rumusan masalah yang dibahas yaitu kendala dalam perjanjian sewa kapal Tugboat dan Barge 230 feet sebagai alat angkut muatan batu boulder dan upaya hukum dalam mengatasi kendala dalam perjanjian sewa kapal Tugboat dan Barge 230 feet sebagai alat angkut muatan batu boulder. Kesimpulan dalam penelitian ini, mengenai kendala dalam perjanjian sewa kapal Tugboat dan Barge 230 feet sebagai alat angkut muatan batu boulder yaitu kurangnya kesadaran hukum pihak kedua dalam memahami isi klausul perjanjian khususnya Pasal III dan X dan tidak menuangkan ke dalam akta otentik sehingga tidak mendapat penjelasan dari Notaris mengenai isi-isi dari klausul perjanjian, sehingga mengakibatkan terjadinya sengketa bagi para pihak dalam perjanjian yang telah disepakati. Upaya hukum mengatasi kendala dalam perjanjian sewa kapal Tugboat dan Barge 230 feet sebagai alat angkut muatan batu boulder di wilayah perairan Indonesia dengan menerapkan itikad baik dalam melaksanakan prestasi (hak dan kewajiban) dan menuangkan perjanjian sewa menyewa tersebut ke dalam akta otentik dihadapan Notaris.